The american tradition in literature. Vol.1 / George Perkins, Barbara Perkins - Perkins, George [et.al] (1994)
The narrative of CAbezas de vaca, tje coming of other sick to us the next day, the general history of Virginia, New England, and the summer isles, of their voyage, and how they passed the sea, and of their safe arrival at Cape Cod, meditations, divine and moral, a narrative of the captivity and restorations of Mrs MAry Rowlandson upon wedlock, and Death of Children, a fig for thee oh! Deaath, the life of John Winthrop, the journal of Madam Knight, Sarah Pierrepont, what reason teaches concerning creation.